Synthesis, Evaluation and in silico studies of 1,8-Naphthyridine derivatives against antimicrobial activity - Sakshi Sachdevaa, Sonam Bhatia,a Amit Mittala, Manish Sinhab (Journal of Applied Pharmaceutical Science, 2015)
In present studies a series of novel 1,8-Naphthyridine derivatives (3a-3f) have been synthesized using nalidixic acid as a starting material. The structures of the compounds were supported by FT-IR, 1H NMR and Mass spectral data. All the synthesized compounds have been evaluated in vitro for their antibacterial activities against several strains of microbes using agar dilution method. The synthesized compounds had moderate to good antibacterial activity. Molecular docking studies reveal that 1,8-Naphthyridine scaffold shared structural complimentary with DNA Gyrase B. Further, TOPKAT analysis on Ames mutagenicity model had shown that this class of compounds have least probability of showing toxicity on experimental animal models.
Keywords: 1,8-Naphthyridine, Nalidixic acid, Antimicrobial activity, Ames mutagenicity, Molecular docking, QSTR, Structure based design.